Adherence of Helicobacter pylori to the Gastric Mucosa - Marguerite Clyne; Brendan Drumm (Canadian Journal of Gastroenterology)
Bacterial adhesion to the intestinal epithelium is a critical initial step in the pathogenesis of many enteric diseases. Helicobacter pylori is a duodenal pathogen that adheres to the gastric epithelium and causes gastritis and peptic ulceration. The mechanism by which H pylori causes disease has not yet been elucidated but adherence to the gastric mucosa is thought to be an important virulence determinant of the organism. What is known about adherence of H pylori to the gastric mucosa is summarized. Topics discussed are the mechanism of H pylori adherence; in vitro and in vivo models of H pylori infection; and adherence and potential adhesins and receptors for H pylori.